Caracterización del comportamiento físico, químico y mecánico de los aceites utilizados en las transmisiones automáticas de los vehículos Hyundai y Kia. Latacunga. - Andrango Pachacama, Felix Rene (2022)
The research carried out had the need to verify the physical, chemical and mechanical behavior of the oils used in the automatic transmissions of Hyundai and Kia vehicles; With the investigative process it is determined that the temperature greater than 95 ° C, and the journey through irregular paths causes the loss of lubricant properties and the wear of the internal mechanical parts of the automatic gearboxes of the car brands in question. . Automatic gearboxes today are the most used due to the comfort they present, however, it is necessary to make owners aware of the semi-annual maintenance that has a cost of $ 450, that doing it properly under the parameters of the maintenance guide preventive and corrective allow to avoid long-term damages and that contemplate expenses outside the proposed budget. It is worth mentioning that the cost per billing (COMF) is $8.22 and if fault correction is required (COEF) the cost is $1191.78. The focus of the research is to establish adequate knowledge about automatic gearboxes, to optimize the performance of the components used for their operation, allowing to eliminate the degradation and premature aging of internal elements and hydraulic fluid, to obtain of desired results, the investigation was established in two brands of vehicles that offer the same work performance, in this way the viability of the investigation is ensured, obtaining real results that allow improving its operation. Finally, according to the analysis of the physical, chemical and mechanical characteristics, the structuring of a maintenance guide for its application in the workshop is contemplated.